Integration of a Galdieria plasma membrane sugar transporter enables heterotrophic growth of the obligate photoautotrophic red alga Cynanidioschyzon merolae - Takayuki Fujiwara (Plant Direct, 2019)
Abstract The unicellular thermoacidophilic red alga Cyanidioschyzon merolae is an emerging model organism of photosynthetic eukaryotes. Its relatively simple genome (16.5 Mbp) with very low‐genetic redundancy and its cellular structure possessing one chloroplast, mitochondrion, peroxisome, and other organelles have facilitated studies. In addition, this alga is genetically tractable, and the nuclear and chloroplast genomes can be modified by integration of transgenes via homologous recombination. Recent studies have attempted to clarify the structure and function of the photosystems of this alga. However, it is difficult to obtain photosynthesis‐defective mutants for molecular genetic studies because this organism is an obligate autotroph. To overcome this issue in C. merolae, we expressed a plasma membrane sugar transporter, GsSPT1, from Galdieria sulphuraria, which is an evolutionary relative of C. merolae and capable of heterotrophic growth. The heterologously expressed GsSPT1 localized at the plasma membrane. GsSPT1 enabled C. merolae to grow mixotrophically and heterotrophically, in which cells grew in the dark with glucose or in the light with a photosynthetic inhibitor 3‐(3,4‐dichlorophenyl)‐1,1‐dimethylurea (DCMU) and glucose. When the GsSPT1 transgene multiplied on the C. merolae chromosome via the URACm‐Gs selection marker, which can multiply itself and its flanking transgene, GsSPT1 protein level increased and the heterotrophic and mixotrophic growth of the transformant accelerated. We also found that GsSPT1 overexpressing C. merolae efficiently formed colonies on solidified medium under light with glucose and DCMU. Thus, GsSPT1 overexpresser will facilitate single colony isolation and analyses of photosynthesis‐deficient mutants produced either by random or site‐directed mutagenesis. In addition, our results yielded evidence supporting that the presence or absence of plasma membrane sugar transporters is a major cause of difference in trophic properties between C. merolae and G. sulphuraria.